2003
DOI: 10.1016/s0168-6496(02)00460-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial composition of murine fecal microflora is indigenous and genetically guided

Abstract: The gastrointestinal tract and the microbes colonizing it form a complex ecosystem that has various effects on the well-being of the host. In addition to acute infections, the composition of the gastrointestinal microbiota has been suspected to influence the etiopathogenesis of many chronic diseases, such as rheumatoid arthritis and inflammatory bowel diseases. It has been suggested that the bacterial colonization of the gastrointestinal tract is genetically determined. Using gas-liquid chromatography of bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 28 publications
(36 reference statements)
8
48
0
Order By: Relevance
“…This finding was also noted in the stool samples of other individuals (Tannock et al, 2000) and in other animals, such as dogs, chickens and mice (Zhu et al, 2002;Toivanen et al, 2001;Vaahtovuo et al, 2003). These data show the dependence of the bacterial population on the host animal's digestive system.…”
Section: Fingerprinting Methods Ssu Rdna: Dgge Tgge Ttge Sscp and supporting
confidence: 65%
See 1 more Smart Citation
“…This finding was also noted in the stool samples of other individuals (Tannock et al, 2000) and in other animals, such as dogs, chickens and mice (Zhu et al, 2002;Toivanen et al, 2001;Vaahtovuo et al, 2003). These data show the dependence of the bacterial population on the host animal's digestive system.…”
Section: Fingerprinting Methods Ssu Rdna: Dgge Tgge Ttge Sscp and supporting
confidence: 65%
“…SSU rRNA-based profiles of several other methods, such as cellular fatty acid composition (Toivanen et al, 2001;Vaahtovuo et al, 2003) or C + G DNA content (Apajalahti et al, 2002), have been used successfully to investigate changes in bacterial populations of the gastrointestinal tract. However, compared with SSU rRNA-based methods, these methods provide no phylogenetic information.…”
Section: Non-ssu Rrna-based Profilingmentioning
confidence: 99%
“…Also, differences in the gut microbiota between inbred mouse strains show that it is to a great extent defined by genotype (31)(32)(33). Even though the gut microbiota is influenced by its surroundings during early life, once it is established, it remains relatively stable (34).…”
mentioning
confidence: 99%
“…Studies with mice (Vaahtovuo et al, 2001(Vaahtovuo et al, , 2003Zoetendal et al, 2001;Nones et al, 2009), human IBD patients and healthy subjects (Frank et al, 2007) have shown that the host genotype affects the composition of the bacterial community of the intestine. The reduced number of caecal bacteria observed in Il10 -/-compared to C57 mice, before clinical signs of colitis, is likely to be associated with the genotype.…”
Section: Effect Of Host Genotype On Caecal Bacteriamentioning
confidence: 99%